Avaliação dos processos de seleção utilizados nos programas de fomento a inovação nas micro e pequenas empresas da fundação de amparo à pesquisa do Rio Grande do Norte - Varella, Sergio Ramalho Dantas (2013)
Technological innovation promotes the generation of economic value by creating a new product, process or organizational management model, being classified as dynamic and multidimensional. Government intervention has the role of acting through government grant programs to foster the integration of innovative processes in small companies, due to the high costs and risks of development, strengthening the country`s economy in this phase. The distribution of this grant is determined by criteria, based especially in subjective judgments, which are based on the beliefs and perceptions about the technological opportunities and market actors involved in the process, being very difficult to measure the probability of success of the project under evaluation. This study aims to identify the most relevant selection criteria that must be inserted in grants programs at Rio Grande do Norte executed by Fundação de Pesquisa do Rio Grande do Norte (FAPERN). Initially, there was a systematization of 18 countries, covering 41 programs in foreign countries and 29 in Brazil. Based on the data collected, we conducted one survey containing four programs of FAPERN (INOVA I, INOVA II , INOVA III and INOVA IV), covering 44 companies and analyzing their responses according to the Likert scale , obtaining the degree of importance given by the respondent to each of the criteria in the questionnaire . As a result, drew up a proposal for new criteria to be used in the next FAPERN´s grants, containing 13 new criteria. It is expected, therefore, to contribute to a better spending of public funds invested in companies subsidized in Brazil